Aplikasi Micro-organisme Lokal Terhadap Pertumbuhan dan Produksi Tanaman Cabai Di Bawah Tegakan Kelapa - Tjokrodiningrat, Suryati; Abdullatif, Zauzah; Abdullah, Hayun; Haryanto, Sugeng; Syafie, Yunus; Melati, Rima (Universitas Khairun, 2024)
The coconut plantations in Maffa village are spaced approximately 7 x 9 meters apart, providing enough room for the chili plants to grow. The shading from the coconut plants, at about 45 percent, is suitable for the growth of chili plants. An experiment was conducted to observe the application of local micro-organisms on chili and its influence on the phenotype of chilies in coconut-sheltered conditions also the resistance to anthracnose attacks.. The experiment was held in the Mafa village coconut plantation from November 2022 to March 2023. The research was implemented using factorial treatment based on Randomized Block Design with 30 percent and 45 percent coconut shelter respectively, and the concentration of local micro-organisms is 5ml and 10ml per liter of water, respectively. The observational data was analyzed using the F-test and a treatment difference test at a five percent significance level. The research findings indicated that shade level and local microorganism concentration significantly impacted, the number of brunches, and the fruit weight. The highest chili production was 476.39 g tree-1 harvest-1.Keywords: Chili, micro-organism, coconut plantation.